Mechanical Evaluation of Adjunctive Fixation for Prevention of Periprosthetic Femur Fracture With the Zurich Cementless Total Hip Prosthesis. Issue 5 (3rd June 2013) - Pozzi, Antonio; Peck, Jeffrey N.; Chao, Peini; Choate, Christina J.; Barousse, Dan; Conrad, Bryan
Abstract Objective To evaluate whether cerclage wire or a lateral plate increases the peak‐torque load to failure, compared to femora without adjunctive fixation, in femora implanted with Zurich Cementless stems. Study Design In vitro biomechanical study. Sample Population Paired femora from adult dogs (n = 24) weighing 28–35 kg. Methods Pairs of femora were implanted with a stem and randomly assigned to 2 treatment groups: cerclage or plate. Within each pair, either 3 loop cerclage wires or a laterally applied 12‐hole Advanced Locking Plate System 10‐mm plate (ALPS 10) were implanted in a femur, whereas the contralateral femur acted as control with no adjunctive fixation. After application of a static axial load each specimen was loaded to failure in torsion. Peak torque load at failure was compared between femora with each adjunctive fixation and the control using a paired t‐test; P < .05 was considered significant. Results In both treatment groups, femora with adjunctive fixation failed at higher loads compared to the femora without fixation; however, significant difference in peak torque at failure between treated femora and control was found only in the plated group (P < .05). Femora implanted with plates and with cerclage were 13.9% and 7.2% stronger in torsion than the femora without fixation, respectively. Conclusions Adjunctive fixation with a laterally applied ALPS 10 may aid in the prevention of peri‐prosthetic fractures associated with Zurich Cementless medium stems.